PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN KINEMASTER PADA MATERI SUMBER ENERGI PANAS DI KELAS V SDN 42 PEKANBARU - Nurhaliza, Siti; Laili Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The teacher's lack of ability to convey heat energy source material only through two-dimensional visual media. Learning videos have the potential to help students understand the material by involving students in learning to increase student learning motivation. Therefore, researchers are interested in developing learning media in the form of learning videos which are expected to help the needs of teachers and students in learning material at any time. This research is research and development using a 4D model which is simplified into three stages, namely (Define, Design, and Development). the data collection instrument was a questionnaire given to material experts, media experts, and linguists to test the validity. the type of data obtained from the research results is qualitative data which is analyzed using quantitative data in the form of numerical data and interpreted with guidelines for assessment criteria to determine product quality. The results of this study, produce learning video media products that meet very valid criteria with an average score media experts 97%, material experts 100%, and language experts 96.8% with very valid criteria.